Vertical arrays of SiNWs-ZnO nanostructures as high performance electron field emitters - Devarapalli, Rami Reddy; Shinde, Deodatta R.; Barka-Bouaifel, Fatiha; Yenchalwar, Sandeep G.; Boukherroub, Rabah; More, Mahendra A.; Shalke, Manjusha V. (Journal of Materials Chemistry, 2012)
Multicomponent hybrid materials of nanostructured building blocks are essential for the development of complex devices and advanced applications due to their role as either functional or interconnecting elements. This study introduces a simple and cost effective strategy for the synthesis of vertical arrays of silicon nanowires and ZnO nanostructures (nanorod and multipod structures). Formation of vertical nanostructured arrays is confirmed by SEM and HRTEM imaging as well as XRD and Raman measurements. We have investigated field emission properties of the as-synthesized vertical nanostructured arrays. Our results show that these SiNWs-ZnO nanostructures are highly efficient and stable field emitters.